Synergic Development of Organizations with Employee Aspirations - Subramanian, K. R. (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2017)
Employee involvement in organization development takes place when their aspirations are fulfilled through work. Even with a carefully planned compensation and incentive program the attrition rate in some organizations is high. When management genuinely takes care of employee aspirations the resultant synergy is reflected in customer satisfaction and product quality. Managing employee aspirations takes genuine interest and requires a structure to help employees and plan for their development by Assessment, alignment with business needs and taking steps for development of people. Organizations can help employees sharpen and develop their key skills and values and provide important feedback information to reshape their goals in alignment with the business needs of the organization. Organizational barriers to growth and Professional development of employees leads to lack of commitment and eventual separation of employees. This paper explores such barriers to employee involvement and how synergic development can take place.